Improved properties of hybrid Al-CNTs via h-BNs coated with ag and ni for ball bearings - Waheed S. Barakat; Ahmed Samir; Omayma A. Elkady; Mohamed Abu-Okail; Abdelkarim Y. A. Mohamed; A. EL-Nikhaily; A. M. I. Abu-Oqail (Scientific Reports)
Abstract Ball bearings face numerous challenges under harsh operating conditions of elevated pressure between the balls and other contacting parts of the bearing like drop in tribological properties. To address these challenges, this paper presents the first successful experimental investigation of incorporating an innovative hexagonal boron nitride (h-BN) into Aluminum-Carbon nanotube (Al-0.6 wt% CNTs) nanocomposites. This was achieved using electroless chemical deposition technique to coat the materials with silver (Ag) and nickel (Ni), improving the wettability and dispersion between the matrix and reinforcement. Various h-BN ratios (2, 4, 6, 8 and 10 wt%) are incorporated and consolidated through high-energy ball milling and hot compaction techniques. The produced samples were tested and analyzed physically, mechanically, tribologically, and microstructurally. X-ray diffraction (XRD) and scanning electron microscope (SEM) analyses were used to explore the new morphologies and structures. The study delves into density, hardness, and wear resistance. The optimal h-BN content is determined to be 8 wt%, enhancing wettability and dispersion within the Al-CNTs matrix. Thus, the properties of hardness, compressive strength, wear rate, and COF at 8 wt% of h-BN content were enhanced by 105%, 60%, 74.5%, and 78.5%, respectively, compared to pure Al. This is due to the uniform scattering of h-BN nanoparticles across the entire surface, despite a significant decrease in relative density. In conclusion, the combination of mechanical alloying, electroless deposition, and hot compaction techniques proves to be effective in producing Al-CNTs/h-BN nanocomposites coated with Ag and Ni nanoparticles.